New insight into the deep structure of Antarctic Peninsula continental margin by methods of 2D gravity/magnetic modelling and 3D seismic tomography - T. Yegorova; V. Bakhmutov; V. Gobarenko; A. Lyashchuk (Ukrainian Antarctic Journal, 2009)
The Antarctic Peninsula, one of several terrains of Western Antarctica, is a Mesozoic magmatic arc at the southeastern Pacific margin. In order to investigate the structure of the crust and uppermost mantle of Antarctic Peninsula continental margin we have developed joint geophysical models by 2D gravity and magnetic modelling along two most representative and lengthy seismic refraction lines, acquired by Polish Academy of th Sciences in 1980-1990 . Resulting model along line I-I (along the DSS line 12), crosssing the Antarctic Peninsula margin near the Anvers Island, shows the features of passive continental margin of convergent type. The joint model on line II-II, passing from the Drake Passage through the South-Shetland Trench/Islands system and Bransfield Strait to Antarctic Peninsula, indicates continental margin structure of active style, caused by recent subduction and on-going continental rifting in the Bransfield Strait. This subduction activity is responsible to the stripes of gravity and magnetic anomalies along the Antarctic Peninsula shelf, caused by many batholits and plutons of mafic rocks (gabbro and diorites), intruded into the crust due to partial melting of the upper mantle caused by south-eastward progradation of subduction front. On-going tectonic processes within the South Shetland Islands – Bransfield Strait block relate to mobilization of the upper mantle substance characterized by the lowest density (3.18 g/cm ) against the uppermost mantle densities of 3.21 and 3.30 g/cm revealed beneath the oceanic crust and Antarctic Peninsula continental crust respectively. To study the lithosphere structure of the region of Antarctic Peninsula and adjoining sea-water areas we implemented the seismic tomography method which is based on Backhus-Gilbert approximation and uses the data on earthquake foci and time arrival of P-waves recorded by network of seismic stations. On the first stage only 27 events from the International Seismology Center (ISC) for the period 1992-2005, recorded by five permanent seismic stations, were used. Preliminary computation of P-wave velocity field results in construction of a velocity section at the depth of 100 km. It shows a low-velocity zone, which covers the major part of the Drake Passage, South-Shetland Islands and western part of the Scotia Sea.